Photodynamic Therapy for the Treatment and Diagnosis of Cancer–A Review of the Current Clinical Status - Gunaydin, Gurcan; Gedik, M. Emre; Ayan, Seylan (Frontiers in Chemistry, 2021)
Photodynamic therapy (PDT) has been used as an anti-tumor treatment method for a long time and photosensitizers (PS) can be used in various types of tumors. Originally, light is an effective tool that has been used in the treatment of diseases for ages. The effects of combination of specific dyes with light illumination was demonstrated at the beginning of 20th century and novel PDT approaches have been developed ever since. Main strategies of current studies are to reduce off-target effects and improve pharmacokinetic properties. Given the high interest and vast literature about the topic, approval of PDT as the first drug/device combination by the FDA should come as no surprise. PDT consists of two stages of treatment, combining light energy with a PS in order to destruct tumor cells after activation by light. In general, PDT has fewer side effects and toxicity than chemotherapy and/or radiotherapy. In addition to the purpose of treatment, several types of PSs can be used for diagnostic purposes for tumors. Such approaches are called photodynamic diagnosis (PDD). In this Review, we provide a general overview of the clinical applications of PDT in cancer, including the diagnostic and therapeutic approaches. Assessment of PDT therapeutic efficacy in the clinic will be discussed, since identifying predictors to determine the response to treatment is crucial. In addition, examples of PDT in various types of tumors will be discussed. Furthermore, combination of PDT with other therapy modalities such as chemotherapy, radiotherapy, surgery and immunotherapy will be emphasized, since such approaches seem to be promising in terms of enhancing effectiveness against tumor. The combination of PDT with other treatments may yield better results than by single treatments. Moreover, the utilization of lower doses in a combination therapy setting may cause less side effects and better results than single therapy. A better understanding of the effectiveness of PDT in a combination setting in the clinic as well as the optimization of such complex multimodal treatments may expand the clinical applications of PDT.